THE EFFECT OF OCCUPATIONAL SAFETY AND HEALTH MANAGEMENT (K3) ON WORK PRODUCTIVITY OF EMPLOYEES: PENGARUH MANAJEMEN KESELAMATAN DAN KESEHATAN KERJA (K3) TERHADAP PRODUKTIVITAS KERJA KARYAWAN - Sinollah Sinollah; Achmad Zaki (International Journal of Economics and Management Research, 2022)
This study aims to determine the effect of the implementation of Occupational Health and Safety management (K3) on employee productivity at PG. Ngadirejo Kediri. To achieve this goal, this study uses quantitative research with a questionnaire as the main instrument in collecting data. To answer the hypothesis using multiple linear regression analysis. Based on tests conducted with multiple linear regression, it is evident that the variable level of occupational safety (X1) and the variable level of occupational health (X2) has a significant effect on employee productivity (Y) either partially or simultaneously. To reduce the risk of accidents such as fires, piles of mill residues containing flammable chemicals. That jam, PG. Ngadirejo Kediri should strive so that the remnants of the mill can be immediately utilized/sold.